2021
DOI: 10.31234/osf.io/yubkz
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Linguistic Representation and Processing of Copredication

Abstract: This thesis addresses the lexical and psycholinguistic properties of copredication. In particular, it explores its acceptability, frequency, cross-linguistic and electrophysiological features. It proposes a general parsing bias to account for novel acceptability data, through which Complex-Simple predicate orderings are degraded across distinct nominal types relative to the reverse order. This bias, Incremental Semantic Complexity, states that the parser seeks to process linguistic representations in increment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 172 publications
4
50
0
1
Order By: Relevance
“…The only current work which has empirically tested the effects of predicate ordering on copredication acceptability is Murphy's (2019Murphy's ( , 2021 experiments, which found that copredicated sentences exhibiting a Concrete-Abstract predicate order (Murphy 2019), and also a Simple-Complex order (Murphy 2021), were significantly more acceptable than sentences exhibiting an Abstract-Concrete and Complex-Simple order (see also Murphy 2017). This seems to match the general acceptability contrasts reviewed throughout this article.…”
Section: Incremental Semantic Complexitysupporting
confidence: 54%
See 2 more Smart Citations
“…The only current work which has empirically tested the effects of predicate ordering on copredication acceptability is Murphy's (2019Murphy's ( , 2021 experiments, which found that copredicated sentences exhibiting a Concrete-Abstract predicate order (Murphy 2019), and also a Simple-Complex order (Murphy 2021), were significantly more acceptable than sentences exhibiting an Abstract-Concrete and Complex-Simple order (see also Murphy 2017). This seems to match the general acceptability contrasts reviewed throughout this article.…”
Section: Incremental Semantic Complexitysupporting
confidence: 54%
“…The motivation behind this is that these will be the two main factors claimed here to be responsible for copredication acceptability dynamics. They have only recently been empirically investigated in relation to copredication (Murphy 2021), and are yet to be accounted for within present theories.…”
Section: Evaluating Copredicationmentioning
confidence: 99%
See 1 more Smart Citation
“…This may indicate that concrete words predominantly activate higher-order visual regions linked with visual experience, while abstract words, by virtue of lower imageability, require more involvement of frontal associative areas and the core language system. Furthermore, in many studies, a larger amplitude of N400, a well-known ERP index of semantic processing, was obtained for concrete than for abstract words across the scalp [ 7 , 8 , 9 , 10 , 11 ]. Later anterior effects were revealed in visualisation [ 7 ] and imagery tasks [ 10 ]: N700, a component reflecting imagery processing and associating with working memory, was elicited only by concrete words.…”
Section: Introductionmentioning
confidence: 99%
“…), most authors have tried to accommodate this phenomenon within a referentialist/externalist framework, but as Vicente (2021) reviews, these all have a number of issues (although Vicente also comes to an externalist conclusion). Pietroski (2018), Chomsky (2000, Yalcin (2014) and Murphy (2021a) maintain that the phenomenon may require abandoning referential semantics altogether, as maintained here. Internalists point to the centrality of human functional interests and concerns in linguistic reference, undermining the view that these nominals are a mereological sum (forming a 'complex object' in the mindindependent world) or a union of the extensions of different senses.…”
Section: Referring To Impossible Entities With Copredicationmentioning
confidence: 80%